The third species of Meiyingia Holzschuh, 2010 (Coleoptera: Cerambycidae: Cerambycinae: Oemini) from China - Liu, Bin; Wang, Cheng-Bin (Zootaxa, 2016)
Meiyingia holzschuhi sp. nov. (Coleoptera: Cerambycidae: Cerambycinae: Oemini) is described from Guangxi Zhuang Autonomous Region, China. Important morphological characters of the new species are illustrated in color plates. A key to the three known species of the genus is modified to include the new species, and the known distribution of the genus is mapped.